The mass-metallicity relation of interacting galaxies - Michel-Dansac, Leopold (2008)
We study the mass–metallicity relation of galaxies in pairs and in isolation taken from the Sloan Digital Sky Survey-Data Release 4 (SDSS-DR4) using the stellar masses and oxygen abundances derived by Tremonti et al. Close galaxy pairs, defined by projected separation rp < 25 kpc h−1 and radial velocity V < 350 km s−1, are morphologically classified according to the strength of the interaction signs. We find that only for pairs showing signs of strong interactions, the mass–metallicity relation differs significantly from that of galaxies in isolation. In such pairs, the mean gas-phase oxygen abundances of galaxies with low stellar masses (M∗ 109 M h−1) exhibit an excess of 0.2 dex. Conversely, at larger masses (M∗ 1010 M h−1) galaxies have a systematically lower metallicity, although with a smaller difference (−0.05 dex). Similar trends are obtained if g-band magnitudes are used instead of stellar masses. In minor interactions, we find that the less massive member is systematically enriched, while a galaxy in interaction with a comparable stellar mass companion shows a metallicity decrement with respect to galaxies in isolation. We argue that metal-rich starbursts triggered by a more massive component, and inflows of low-metallicity gas induced by comparable or less massive companion galaxies, provide a natural scenario to explain our findings.